Assessment of the Chemical Quality of Recreational Bathing Water in Argentina by Health Risk Analysis - Peluso, Fabio Oscar (2012)
Del Azul creek (Argentina) is a natural water body used for recreational bathing in which heavy metals and pesticides have been detected. The aim of the study is to estimate the probabilistic non-cancer and cancer risks by recreational bathing, applying U.S. Environmental Protection Agency models for aggregated (exposure through accidental oral intake of water and dermal contact) and cumulative risks (combined exposure to groups of substances) for bathers of 5, 10, 15, and 20 years old. Bathing in Del Azul creek does not generate risks at the concentrations and the exposure scenarios considered. Cypermethrin and arsenic and arsenic and heptachlor were the riskiest non-cancer and cancer substances, respectively. Our study highlights the importance of considering both routes of exposure because of the great significance of the dermal route and because of the variability of population characteristics, as it has been stated in other studies. These considerations are highly significant for Argentina, where the quality of recreational water for other than microbiological causes is frequently evaluated based only on the harmful oral intake and applied to a hypothetical individual representative of the population.